2019
DOI: 10.1111/hiv.12715
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral drug use as the main barrier to hepatitis C treatment uptake in HIV‐infected patients

Abstract: ObjectivesOur objective was to identify patient factors associated with being untreated for hepatitis C virus (HCV) infection in HIV-coinfected patients. MethodsA prospective longitudinal study was carried out. HIV-infected patients with active chronic HCV infection included in the HERACLES cohort (NCT02511496) constituted the study population. The main study outcome was receipt of HCV direct-acting antiviral (DAA) treatment from 1 May 2015 to 1 May 2017. The population was divided into patients who were recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…A study of HCV screening of patients in HIV care in the United States found that 77.9% were not tested for HCV and that only 17.8% were initiated onto treatment [31]. A prospective cohort in Spain found that while more than 60% were started on HCV treatment, recent PWID and those on opioid substitution therapy had lower rates compared with other groups, which is consistent with our results [32]. An Australian cohort of co‐infected patients also found that rapid scale‐up of DAA treatment was possible in a short time and these results demonstrate that micro‐elimination in this population is possible [33].…”
Section: Discussionsupporting
confidence: 89%
“…A study of HCV screening of patients in HIV care in the United States found that 77.9% were not tested for HCV and that only 17.8% were initiated onto treatment [31]. A prospective cohort in Spain found that while more than 60% were started on HCV treatment, recent PWID and those on opioid substitution therapy had lower rates compared with other groups, which is consistent with our results [32]. An Australian cohort of co‐infected patients also found that rapid scale‐up of DAA treatment was possible in a short time and these results demonstrate that micro‐elimination in this population is possible [33].…”
Section: Discussionsupporting
confidence: 89%
“…Among studies conducted in settings without universal DAA-access, individuals with frequently missed visits and PWID were less likely to receive DAA [8–11], similar to our findings. Additionally, those with advanced fibrosis or cirrhosis more often received DAAs, likely owing to the specific restrictions put in place in these settings [8–11]. Regarding alcohol use, similar to what we observed, severe alcohol use was associated with a lower DAA-uptake in a study in HCV-infected individuals receiving opioid agonist therapy [21], which was not confirmed in a smaller study among HIV-positive PWID [22].…”
Section: Discussionsupporting
confidence: 89%
“…Among studies conducted in settings without universal DAA-access, individuals with frequently missed visits and PWID were less likely to receive DAA [8][9][10][11], similar to our findings. Additionally, those with advanced fibrosis or cirrhosis more often received DAAs, likely owing to the specific restrictions put in place in these settings [8][9][10][11].…”
Section: Barriers To Direct-acting Antiviral Treatment Uptakesupporting
confidence: 89%
See 1 more Smart Citation
“…1 A multicenter, observational prospective cohort study (N = 3075) evaluated receipt of HCV treatment for patients co-infected with HCV and HIV. 2 The primary outcome was initiation of HCV treatment with DAAs; 1957 patients initiated therapy, while 1118 did not. Significant independent risk factors for noninitiation of treatment included age younger than 50 years, a history of IV drug use, and use of opioid substitution therapy (OST).…”
Section: Exclusive Evidence Summarymentioning
confidence: 99%